TM6SF2 E167K variant decreases PNPLA3-mediated PUFA transfer to promote hepatic steatosis and injury in MASLD - Baokai Sun; Xiaoqian Ding; Jie Tan; Jie Zhang; Xueru Chu; Shuimi Zhang; Shousheng Liu; Zhenzhen Zhao; Shiying Xuan; Yongning Xin; Likun Zhuang (Clinical and Molecular Hepatology, 2024)
Backgrounds/Aims Transmembrane 6 superfamily member 2 (TM6SF2) E167K variant is closely associated with the occurrence and development of metabolic dysfunction-associated steatotic liver disease (MASLD). However, the role and mechanism of TM6SF2 E167K variant during MASLD progression are not yet fully understood. Methods The Tm6sf2167K knock-in (KI) mice were subjected to high-fat diet (HFD). Hepatic lipid levels of Tm6sf2167K KI mice were detected by lipidomics analysis. Thin-layer chromatography (TLC) was used to measure the newly synthesized triglyceride (TG) and phosphatidylcholine (PC). Results The TM6SF2 E167K variant significantly aggravated hepatic steatosis and injury in HFD-induced mice. Decreased polyunsaturated PC level and increased polyunsaturated TG level were found in liver tissue of HFD-induced Tm6sf2167K KI mice. Mechanistic studies demonstrated that the TM6SF2 E167K variant increased the interaction between TM6SF2 and PNPLA3, and impaired PNPLA3-mediated transfer of polyunsaturated fatty acids (PUFAs) from TG to PC. The TM6SF2 E167K variant increased the level of fatty acid-induced malondialdehyde and reactive oxygen species, and decreased fatty acid-downregulated cell membrane fluidity. Additionally, the TM6SF2 E167K variant decreased the level of hepatic PC containing C18:3, and dietary supplementation of PC containing C18:3 significantly attenuated the TM6SF2 E167K-induced hepatic steatosis and injury in HFD-fed mice. Conclusions The TM6SF2 E167K variant could promote its interaction with PNPLA3 and inhibit PNPLA3-mediated transfer of PUFAs from TG to PC, resulting in the hepatic steatosis and injury during MASLD progression. PC containing C18:3 could act as a potential therapeutic supplement for MASLD patients carrying the TM6SF2 E167K variant.